Reading Illness from “The Dead Cold Light of Tomorrow”: Katherine Anne Porter’s Pale Horse, Pale Rider in the Times of COVID-19 - Rebeca Gualberto Valverde (Miscelánea: A Journal of English and American Studies, 2022)
The aim of this study is to suggest a new assessment of Katherine Anne Porter’s semi-autobiographical account of her near-death experience with the 1918 flu, Pale Horse, Pale Rider (1939), considered by many as the paradigmatic American narrative of that pandemic. Following the trend set by most critics of Porter, this article explores the intersections of memory and fiction in the novella, but shifting attention to our present-day response, assessed as a critical tool that provides renewed insight into the mysteries of Porter’s late-modernist text. Revisited in a context in which cultural memories of the 1918 influenza have been awakened by our own traumatic experience with COVID-19, this article seeks to probe the uncertainties in Porter’s aestheticized trauma narrative. The aim is to investigate the hypothesis that our contemporary reading of Pale Horse, Pale Rider illuminates the modernist obscurities in the text and, in consequence, raises the possibility of transcending the limitations of language and myth exhibited in the text, providing new meanings through connection and remembrance.